Медиевалистический текст в современной русской литературе как ответ на поиски идентичности после распада СССР - Pacyno, Witold (Studia Rossica Posnaniensia, 2019)
The aim of the article is defining the cause of popularity of medievalism in contemporary Russian literature as well as describing an impact of the images of the Middle Ages in Russian medievalist texts on the national identity after the collapse of the Soviet Union.